Pengaruh Metode Pembelajaran Tematik terhadap Minat Belajar Siswa di SDN 32 Bukit Kandung - Lusia, Selvi; Hidayani, Yerni; Fitriani, Fitriani (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to analyze the effect of thematic learning methods on students' learning interest at SDN 32 Bukit Kandung. This research employs a classroom action research (CAR) method using the Kemmis and McTaggart model, consisting of two cycles with stages of planning, action implementation, observation, and reflection. The research subjects were 25 fourth-grade students. Data collection techniques included observations, learning interest questionnaires, teacher interviews, and documentation throughout the learning process. Data were analyzed qualitatively and quantitatively to examine changes in students' learning interest before and after the implementation of thematic learning methods. The findings indicate that the thematic learning method significantly enhances students' learning interest. Students became more active, enthusiastic, and showed higher engagement in learning compared to conventional methods. This improvement was attributed to a more contextual, interactive, and integrative approach aligned with students' real-life experiences. However, challenges in implementing this method include teachers' readiness to design engaging thematic materials and the availability of suitable learning resources. Therefore, the thematic learning method can serve as an effective alternative strategy to improve elementary school students' learning interest when implemented optimally and supported by adequate facilities.